Critical role of formaldehyde during methanol conversion to hydrocarbons - Yue Liu (Nature Portfolio, 2019)
The recognition of the importance of HCHO in methanol to olefins (MTO) makes it imperative to quantify its concentration in the reaction and distribution over the catalyst bed. Here the authors quantify the concentration level of HCHO and its distribution along the catalyst bed in MTO, and explores its role in methanol conversion.